Simulation of sub-drains performance using visual MODFLOW for slope water seepage Problem - T Baharuddin, M F; Tajudin, S A A; Z Abidin, M H; Yusoff, N A (IOP Publishing, 2016)
Numerical simulation technique was used for investigating water seepage problem at the Botanic Park Kuala Lumpur. A proposed sub-drains installation in problematic site location was simulated using Modular Three-Dimensional Finite Difference Groundwater Flow (MODFLOW) software. The results of simulation heads during transient condition showed that heads in between 43 m (water seepage occurred at level 2) until 45 m (water seepage occurred at level 4) which heads measurement are referred to mean sea level. However, elevations measurements for level 2 showed the values between 41 to 42 m from mean sea level and elevations for level 4 between 42 to 45 m from mean sea level. These results indicated an increase in heads for level 2 and level 4 between 1 to 2 m when compared to elevations slope at the level 2 and level 4. The head increases surpass the elevation level of the slope area that causing water seepage at level 2 and level 4. In order to overcome this problems, the heads level need to be decrease to 1 until 2 m by using two options of sub-drain dimension size. Sub-drain with the dimension of 0.0750 m (diameter), 0.10 m (length) and using 4.90 m spacing was the best method to use as it was able to decrease the heads to the required levels of 1 to 2 m.